Are socially responsible investments profitable? Evidence on performance and volatility in Malaysia - Lim, Shen Khai (2023)
This study utilised various risk-adjusted performance measures, conditional volatility models and an event study methodology to conduct a comprehensive analysis on the profitability of SRI equity indices and mutual funds in Malaysia with sample data ranging from December 2014 to July 2022. The risk-adjusted performance of Malaysian SRIs are statistically indistinguishable from that of conventional investments, which suggests the opportunity of doing as well while doing good. The overall findings for the ratio-based performance measures indicate that the equity SRI indices tend to outperform their conventional counterparts, especially during periods of crisis recovery. Conditional volatility analysis is also conducted on index returns using a GARCH (1,1) and TGARCH (1,1) model. Although short-term transmission is volatility is greater for SRI indices, they experience substantially less systematic risk and lower persistence of volatility clustering compared to conventional indices. SRI index returns also display a leverage effect of a lower magnitude relative to conventional index returns. Lastly, an event study methodology is conducted using the market model and GARCH (1,1) with event dummy to assess the impact of critical economic and environmental events on the returns and conditional volatility of SRI index returns. In terms of economic events, SRI indices displayed sizeable recovery from five days up to a month following the COVID-19 market crash, but also exhibited greater volatility. As for positive environmental news, SRI indices demonstrated a shift from positive to negative returns within the 10-day event window following the ratification of the Paris Climate Accords, and vice versa following the adoption of the Glasgow Climate Pact. No significant evidence was found on the effects of negative environmental news on SRI index return and conditional volatility.